Pelatihan Dan Penerapan Sistem Surat Digital Untuk Meningkatkan Efisiensi Administrasi di Kantor Kepala Desa Dalu Sepuluh - Zulham Zulham; Buyung Solihin Hasugian; Muhammad Eka; Sri Wahyuni (Unity Academy, 2025)
The rapid development of information technology, particularly artificial intelligence (AI), requires teachers to integrate digital tools into the learning process. However, many teachers still face difficulties in creating engaging, systematic, and communicative presentation media due to limited time, insufficient design skills, and high administrative workloads. This problem was also found among teachers at SMA Negeri 5 Medan, who mostly relied on conventional presentation media. As a solution, this community service activity was conducted through training on the utilization of the Gamma Application, an AI-based platform that enables automatic presentation creation using text-based commands. A total of 30 teachers participated in this activity. The methods applied included workshops, hands-on practice, and interactive discussion sessions. Teachers were guided from the introduction of Gamma’s features to content development and the production of ready-to-use presentation slides. This activity aimed to improve teachers’ digital competence and support the development of more innovative, attractive, and effective learning media. Its main contribution lies in enhancing teachers’ skills in using AI-based technology and strengthening digital-based learning practices in schools. The results showed that all participants were able to operate the Gamma Application and produce more visually appealing, well-structured, and communicative learning presentations. Furthermore, teachers’ understanding of the role of technology in supporting the learning process significantly improved. Therefore, this activity had a positive impact on the quality of instructional media and teachers’ insights into the use of digital technology.